Cigarette smoke-promoted acquisition of bacterial pathogens in the upper respiratory tract leads to enhanced inflammation in mice. Issue 1 (December 2015) - Voss, Meike; Wonnenberg, Bodo; Honecker, Anja; Kamyschnikow, Andreas; Herr, Christian; Bischoff, Markus; Tschernig, Thomas; Bals, Robert; Beisswenger, Christoph
Abstract Background Bacterial colonization and recurrent infections of the respiratory tract contribute to the progression of chronic obstructive pulmonary disease (COPD). There is evidence that exacerbations of COPD are provoked by new bacterial strains acquired from the environment. Using a murine model of colonization, we examined whether chronic exposure to cigarette smoke (CS) promotes nasopharyngeal colonization with typical lung pathogens and whether colonization is linked to inflammation in the respiratory tract. Methods C57BL/6 N mice were chronically exposed to CS. The upper airways of mice were colonized with nontypeableHaemophilus influenzae (NTHi) orStreptococcus pneumoniae . Bacterial colonization was determined in the upper respiratory tract and lung tissue. Inflammatory cells and cytokines were determined in lavage fluids. RT-PCR was performed for inflammatory mediators. Results Chronic CS exposure resulted in significantly increased numbers of viable NTHi in the upper airways, whereas NTHi only marginally colonized air-exposed mice. Colonization withS. pneumoniae was enhanced in the upper respiratory tract of CS-exposed mice and was accompanied by increased translocation ofS. pneumoniae into the lung. Bacterial colonization levels were associated with increased concentrations of inflammatory mediators and the number of immune cells in lavage fluids of the upper respiratory tract and the lung. Phagocytosis activity was reduced in whole blood granulocytes and monocytes of CS-exposed mice. Conclusions These findings demonstrate that exposure to CS impacts the ability of the host to control bacterial colonization of the upper airways, resulting in enhanced inflammation and susceptibility of the host to pathogens migrating into the lung.